Impaired KCC2 Function Triggers Interictal-Like Activity Driven by Parvalbumin-Expressing Interneurons in the Isolated Subiculum In Vitro. (14th May 2021) - Anstötz, Max; Fiske, Michael Patrick; Maccaferri, Gianmaria
Abstract: The decreased expression of the KCC2 membrane transporter in subicular neurons has been proposed to be a key epileptogenic event in temporal lobe epilepsy (TLE). Here, we have addressed this question in a reduced model in vitro and have studied the properties and mechanistic involvement of a major class of interneurons, that is, parvalbumin-expressing cells (PVs). When exposed to the KCC2 blocker VU0463271, mouse subicular slices generated hypersynchronous discharges that could be recorded electrophysiologically and visualized as clusters of co-active neurons with calcium imaging. The pharmacological profile of these events resembled interictal-like discharges in human epileptic tissue because of their dependence on GABAA and AMPA receptors. On average, PVs fired before pyramidal cells (PCs) and the area of co-active clusters was comparable to the individual axonal spread of PVs, suggesting their mechanistic involvement. Optogenetic experiments confirmed this hypothesis, as the flash-stimulation of PVs in the presence of VU0463271 initiated interictal-like discharges, whereas their optogenetic silencing suppressed network hyper-excitability. We conclude that reduced KCC2 activity in subicular networks in vitro is sufficient to induce interictal-like activity via altered GABAergic signaling from PVs without other epilepsy-related changes. This conclusion supports an epileptogenic role for impaired subicular KCC2 function during the progression of TLE.